Investigation of film cooling effectiveness enhancement by using corrugated spiral holes - AbdulWahid, Ammar Fakhir (Praise Worthy Prize, 2015)
Film cooling represents one of the important game-changing technologies that has allowed the achievement of today’s high inlet turbine temperature to get high-efficiency gas turbine engines. Shear Stress Transport (SST) K-? was performed to investigate the flow structures and the development process of vortices in different sections (rectangular, hexagonal and circular) of a stationary gas turbine at blowing ratio equal to (0.5, 1.0, 1.5 and 2.0), while the jet film coolinghole angles equal to (90°, 60°, 45° and 30°). It was observed that higher freestream turbulence improves adiabatic effectiveness and heat transfer coefficient for the corrugation film cooling holes design and specially enhancement at holes angle equal to 30° with twisted angle equal to 360° and rectangular corrugation shape. Results show the effectiveness enhancement range of 20.1%-69.3%of the smooth film cooling hole. Numerical calculation of film cooling effectiveness is validated with reported numerical and experimental results